The Impact of the Media Coverage of Sexual Violence on its Victims/Survivors - Taha, Jaidaa (AUC Knowledge Fountain, 2021)
As part of their daily routine, journalists are often assigned to cover accidents or traumatic events to keep the public updated. With the high competition and the constant deadline pressure, reporters are usually pressured to talk to the subjects of these traumatic accidents too soon to publish their stories. This in turn leaves limited room for them to think about how this coverage is affecting their interviewees. This study aims to examine the impact of the media’s coverage of sexual assault on the victims/survivors of the assault themselves. Media outlets often follow stories of sexual violence, tackling a lot of their details yet, it is unclear whether the interaction with journalists or the frames used in this coverage do more harm or good to the subjects of the assault cases in the Egyptian context. Before answering that, a content analysis on three highly popular Egyptian sexual assault cases is conducted to identify the main frames used in the media while reporting assault. Moreover, interviews with journalists are done to discuss the measures and approaches they take while covering these stories. Afterwards, interviews with survivors of sexual assault and activists working on the cause are conducted to reveal why they seek the media, their feelings after the media exposure, the main issues with the media coverage, and so forth.